A synopsis of the Neotropical genus Nephepeltia (Odonata: Libellulidae), including description of a new species, synonymies, and a key to males - Ellenrieder, Natalia Von (Zootaxa, 2014)
Nephepeltia flavipennis (Holotype: Brazil, Rondônia, Governador Jorge Teixeira Municipality, Fazenda Rancho Grande, 10°31’48’’S, 62°48’0’’W, 165 m, J. Wiseman leg., in MNRJ) is described from the Amazon region of W Brazil, Ecuador, and N Peru. A lectotype is designated for N. aequisetis Calvert, 1909. Nephepeltia chalconota is considered to be a junior subjective synonym of N. flavifrons Karsch, 1889, and the subdivision of N. phryne into two subspecies is found to be unjustifiable. Diagnoses, illustrations, a key to males, and an updated map for all known members of the genus are provided.